ECLECTICISM DALAM ARSITEKTUR DALAM TULISAN CHARLES JENCK: TOWARD RADICAL ECLECTICISM - Prajnawrdhi, Tri Anggraini (Jurnal Natah; Vol. 3, No. 2 Agustus 2005, 2012)
Modernization has evidently presented a new perspective and new idea in architecture development. All form of initiatives are concern noticeably to the challenge idea alongside to the advancement of age and enormous technology. The use of hugely machine, beauty and art at architecture in the past has been forgotten and nowdays tend to go behind an creativity which is clean, clear without ornament and clasiffication of form based on function. Yet, in fact, all forms of the enthusiastic and great modernism have also the variety of weakness. The willing to create the architecutre building which is free, abundant sense, plurally enthusiasm and richly meaning has been formulated obviously modernism dogmas and eventually fall into the appeareance of the eclecticism idea or alliance between history and the technology development.
Keywords: modernism, history, idea, art.